Soft Matter Nanoparticles with Reactive Coronal Pentafluorophenyl Methacrylate Residues via Non-Polar RAFT Dispersion Polymerization and Polymerization-Induced Self-Assembly - Pei, Y.; Noy, J.; Roth, P.; Lowe, Andrew (John Wiley & Sons, 2015)
Soft matter nanoparticles exhibiting rich polymorphism with reactive pentafluorophenyl methacrylate (PFPMA) units in their coronae were prepared via non-polar reversible addition-fragmentation chain transfer dispersion polymerization and polymerization-induced self-assembly. Poly(stearyl methacrylate-stat-PFPMA) macro-CTAs, containing up to 12 mol % PFPMA, were used in n-octane and n-tetradecane for the subsequent copolymerization of 3-phenylpropyl methacrylate. Both formulations gave the full, common family of nanoparticles (spheres, worms, and vesicles) as determined by transmission electron microscopy. Reaction of the PFP ester repeating units in the coronal layer of spherical nanoparticles with benzylamine, tetrahydrofurfurylamine, N,N-dimethylethylenediamine, and an amine functional methyl red dye yielded a new library of functional spherical nano-objects. The success of the nucleophilic acyl substitution reactions was confirmed using a combination of 1H/19F NMR and Fourier transform infrared spectroscopies as well as dynamic light scattering.